2019
DOI: 10.1088/2043-6254/ab4804
|View full text |Cite
|
Sign up to set email alerts
|

The prospect of using guava leaf extract for biosynthesizing chitosan nanoparticles

Abstract: Chitosan is polysaccharide polymer used for biomedical applications and food packaging. The aim of this investigation is to produce chitosan nanoparticles (ChNPs) using guava leaf (Psidium guajava L.) extract as green synthesis of nanoparticles using plant leaf extract is ecofriendly and cost-effective approach. The leaves of guava are nontoxic, full of bioactive compounds, and suitable alternative to avoid chemicals used in other methods. Variations in extract preparation method and ratio of chitosan to leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As the type of solvent used in plants extraction affects the amount of the bioactive material in the extract. Water was the most commonly used solvent for extraction of the active compounds from GL because it is safe and economic 53 . Therefore, in this paper, GL were extracted in hot distilled water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the type of solvent used in plants extraction affects the amount of the bioactive material in the extract. Water was the most commonly used solvent for extraction of the active compounds from GL because it is safe and economic 53 . Therefore, in this paper, GL were extracted in hot distilled water.…”
Section: Resultsmentioning
confidence: 99%
“…The leaves were dried before extraction. This is due to the fact that the phenolic compounds and antioxidants are more concentrated in dried plants than in fresh ones 53 , 54 . It has been reported that water extract of GL is rich in glycosides, saponins, tannins, phenols, terpenoids and flavonoids 31 , 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan nanoparticles (Gl-ChNps) were prepared based on ionic gelation interaction between positive charges of chitosan and negative charges of guava leaf function groups. Nanoparticles were optimized following the approach documented in a prior study published by our group [40] that detailed the preparation and characterization procedures of ChNps based on guava leaf extract.…”
Section: Preparation Of Chitosan (05% Ch) and Chitosan Nanoparticles ...mentioning
confidence: 99%
“…The mixture was stirred at 110 rpm for 30 min. For the obtained solution, dynamic light scattering (DLS), transmission electron microscope (TEM), and zeta potential analyses were measured and discussed in detail in our previous study [40]. Chitosan and chitosan nanoparticles coatings were prepared and used fresh.…”
Section: Preparation Of Chitosan (05% Ch) and Chitosan Nanoparticles ...mentioning
confidence: 99%